Formulation of a Ready-to-Cook Soup Mix Using Microencapsulated Protein Hydrolysate Obtained from Pink Perch By-Product - Asha Kumari; Nutan Kaushik; Rasa Slizyte; Khushboo . (Polish Journal of Food and Nutrition Sciences, 2023)
In fast-growing world, people have not enough time for the preparation of food and they have started depending on fast foods. However, consumption of fast foods causes malnutrition and nutrition-related diseases. Thus, there is a need to formulate nutrient-rich products that are easy to cook. In this study, lyophilized protein hydrolysate from pink perch by-product, microencapsulated protein hydrolysate and sun-dried whole fish powder were incorporated in the formulation of ready-to-cook (RTC) soup mixes. The chemical and physical properties, and consumer acceptability of RTC soup mixes were evaluated. The RTC soup mixes exhibited high solubility (41.0 to 43.0%) and non-Newtonian pseudoplastic behavior. RTC soup mix with microencapsulated protein hydrolysate (MPHS) had high overall acceptability among all RTC soup mixes. The accelerated shelf-life testing (40°C, 75% RH) revealed that RTC MPHS mix was stable for 6 days (equivalent to 24 days of storage at room temperature) without any preservatives and sterilization treatment. Therefore, RTC MPHS mix can be used as a nutrient-rich product in protein-deficient populations.